Angola : Technical Assistant Report. - International Monetary Fund. Fiscal Affairs Dept. (Washington, D.C. : International Monetary Fund, 2015)
This Technical Assistance Report on Angola highlights that the Angolan authorities' plan to scale up priority spending will intensify fiscal pressures. The overall fiscal balance is projected to reach a deficit of about 4 percent of GDP in 2014, owing to a temporary decline in oil production. Besides being fiscally costly, fuel subsidies are inefficient and inequitable. They crowd out growth-enhancing spending?Angola's spending in fuel subsidies is roughly the same as outlays in education and 42 percent larger than health-spending countries. In addition, they provide rent seeking opportunities and raise governance challenges. Furthermore, subsidies create incentives for overconsumption and in turn worsen traffic congestion and accidents?after malaria, road accidents are the second leading cause of death in Angola. Moreover, because most of the benefits of fuel price subsidies accrue to well-off households, they reinforce inequality?more than 50 percent of subsidies go to households in the top 20 percent of the income distribution. The authorities plan to reduce fuel subsidies gradually. This report provides a reform option that would eliminate fuel subsidies and result in fiscal savings of 2 percent of GDP.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet